2002
DOI: 10.1111/1467-9817.00158
|View full text |Cite
|
Sign up to set email alerts
|

Parents’ self‐efficacy beliefs, parents’ gender, children’s reader self‐perceptions, reading achievement and gender

Abstract: This study investigated the relationships among parents’ self‐efficacy beliefs, parents’ gender, children’s reader self‐perceptions, reading achievement and gender. This study consisted of 66 students, aged eight and nine, and 92 parents involved in a family literacy project for approximately one year. The study was conducted in a rural area of Eastern Canada. There were three instruments used in this study: a Questionnaire for Parents, a Reader Self‐Perception Scale (RSPS) (Henk & Melnick, 1995), and a standa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
42
3
8

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(55 citation statements)
references
References 16 publications
2
42
3
8
Order By: Relevance
“…Recently, large-scale studies demonstrated that there was a gradual decline for women in taking degrees or pursuing careers in CS and CE in Greek (Papastergiou, 2008) and in America (National Center for Women & Information Technology, 2009). Whether women can successfully involve themselves in computer-based contexts may rely on their individual perceptions (Papastergiou, 2008), gendered identity in the target society (Norton, 2000), and their family and fellowship support (Lynch, 2002). As Markley (1998) pointed out, women could not interact freely due to power differentials in society when they participated in a computer-based course.…”
Section: A Gender and Computer Educationmentioning
confidence: 99%
“…Recently, large-scale studies demonstrated that there was a gradual decline for women in taking degrees or pursuing careers in CS and CE in Greek (Papastergiou, 2008) and in America (National Center for Women & Information Technology, 2009). Whether women can successfully involve themselves in computer-based contexts may rely on their individual perceptions (Papastergiou, 2008), gendered identity in the target society (Norton, 2000), and their family and fellowship support (Lynch, 2002). As Markley (1998) pointed out, women could not interact freely due to power differentials in society when they participated in a computer-based course.…”
Section: A Gender and Computer Educationmentioning
confidence: 99%
“…There are more supportive results in the literature. Lynch (2002) analysed the reader self-perceptions of 8-9 years old students and found that reader self-perception 'social feedback' dimension level of girls is higher than boys'. Also, level of reading attitude and reading test scores are higher than boys'.…”
Section: Conclusion Discussion and Recommendationsmentioning
confidence: 99%
“…Reading Self-Perception is examined in these studies under the following headings: a study of eighth graders' secondary school reading self-efficacy in terms of several variables (İnnalı, 2014), a study on eighth graders' reading self-efficacy in terms of some variables (İnnalı & Aydın, 2014), the effect of sixth grade students' reading attitudes upon reading comprehension (Ünal, 2012), an examination of secondary school students' levels of reader self-perception in terms of gender, grade, reading environment and frequency (Baştuğ & Çelik, 2015), parents' self-efficacy beliefs, parents' gender, children's reader self-perceptions, reading achievement and gender (Lynch, 2002), examining eighth grade students' reading self-efficacy (Uç gun, 2014), investigation of reading attitudes and self-perceptions of students reading on or below grade level (Hogsten & Peregoy, 1999), the effects of the parent volunteer program upon students' self-perception as a reader (Adunyarittigun, 1997), reading self-efficacy and its effects upon literacy (Akar, 2008), a study on reading self-efficacy of secondary school students (K. Özturk, 2015), measuring the reader self-perceptions of adolescents (Henk, Marinak and Melnick, 2012), validity and reliability study on the scale of belief self-efficiency reading comprehension (Epç aç an & Demirel, 2011), the adaptation of the reader self-perception scale to the fourth and fifth grade Turkish students (Yaylı & Duru, 2008), developing reader self-efficacy scale (Ülper, Yaylı and Karakaya, 2013),the adaptation of reader self-perception scale-2 into Turkish (Keskin & Atmaca, 2014)… This study was hoped to make significant contribution to literature because it examines fourth grade students' reader self-perceptions with respect to their gender and preschool educational background. The previous studies generally analysed secondary school students' reader self-perceptions.…”
Section: Verbal Persuasionmentioning
confidence: 99%
“…-all factors prominent in the literacy literature. They failed, however, to mention some factors that appear extensively in the literature: children's personality (Caspi et al, 2003;Judge et al, 1999;Sneed et al, 1994); children's social competencies and classroom behaviors (Alexander et al, 1993;Corsaro and Nelson, 2003;Judge, 2005;McClelland et al, 2000;Miles and Stipek, 2006;Peterson and Swing, 1982;Poskiparta et al, 2003;and Welsh et al, 2001); children's self-concepts and self-efficacy beliefs Bandura, 1993;Bandura and Locke, 2003;Bar-Tal, 1978;Lynch, 2002;Margolis and McCabe, 2004); and children's causal attribution theories and use of achievement strategies (Bar-Tal, 1978;Fredricks et al, 2004;Guthrie and Wigfield, 2000;Onatsu-Arvillomi et al, 2002;Wigfield et al, 2004;Wong and Csikszentmihalyi, 1991).…”
Section: √ Educational Inequality √ Sociocultural Factorsmentioning
confidence: 99%
“…Not mentioned were parenting styles and parents' self-efficacy beliefs, also prominent in the literature (Judge, 2005;Lynch, 2002;McClelland et al, 2000;Räty, 2006;Serpell et al, 2002). Family income and children's home life were brought up in relation to children's academic performance more frequently by the teachers at Lincoln than by those at Douglas, reflecting the greater variation in school composition and community characteristics at Douglas.…”
Section: √ Educational Inequality √ Sociocultural Factorsmentioning
confidence: 99%